PERGESERAN MAKNA MASKULIN DALAM BUDAYA POPULER (STUDI KASUS KAJIAN SEMIOTIKA IKLAN VT X BTS â€œTIME TO SHINEâ€) - Syafikarani, Aisyi (Universitas Komputer Indonesia, 2021)
VT Cosmetics comes with new ad that uses BTS's K-Pop star brand ambassador, the ad represents masculinity as an attribute of popular culture. Therefore, this study aims to analyze how the representation of masculinity as an attribute of popular culture in VT x BTS